A deep analysis of the genetic structure of Ralstonia solanacearum in Brazil reveals not much sex in the population - Santiago, Thaís Ribeiro (2014)
Bacterial wilt, caused by the Ralstonia solanacearum, cause direct and indirect losses in several crops. Planting of resistant varieties is the best option for disease management, but reports of resistance breakdown are commonly found in the literature. Although many years have passed after the first report of this pathogen in Brazil, information on biovars, phylotypes, sequevars and genetic variability of the pathogen is scarce. In the present study isolates were characterized as biovar 1, 2 and 3. Phylotype II is spread throughout Brazil and phylotype I is predominantly found in the North. Seven sequevars were identified: 1, 4, 18, 27, 28, 41 and 50. Moreover, we classified four new sequevars in the phylotype IIB as sequevar 53, 54, 55 and 56. Initially, we used rep-PCR to estimate the variability of the pathogen and 282 haplotypes were obtained. The high number of haplotypes could be due to the occurrence of recombination. Isolates of the South/Southeast/Central regions formed a genetically related cluster. Isolates from the North/Northeast regions formed another group. Gene flow occurs through the transportation of contaminated tubers and seedlings. Genetic differentiation was detected among isolates from tomato and potato collected in the South/Central/Southeast regions. In addition, gene genealogies based on the coalescent process were used to infer about evolutionary mechanisms. We detected evidence of subdivision of phylotypes I, IIA and IIB, but no subdivision by hosts. The gene flow is predominantly from the southern to the northern regions. We confirmed that phylotype II is an ancestral lineage that originated in Brazil and probably phylotype I was recently introduced by anthropogenic actions. Phylotype IIA originated phylotype IIB and this difference was probably due to ecological factors that need to be studied in more detail. Mutation, migration, recombination and selection occur in the population of R. solanacearum in Brazil, however mutation is more important than recombination. We conclude that the use of resistant varieties is a major challenge in all regions and hosts.